Genital pain: algorithm for management - Calixte, Nahomy; Brahmbhatt, Jamin; Parekattil, Sijo (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Chronic testicular pain although becoming very common in our patient population poses a challenge to the physician, the patient and his family. The pathogenesis of chronic orchialgia (CO) is not well understood. The objective of this paper is to review the current literature on chronic testicular pain and its management and to propose an algorithm for its treatment. Abstracts, original papers and review articles were reviewed during a literature search using words such as testicular pain, CO, and microsurgical anatomy of spermatic cord. Chronic scrotal content pain (CSP) is a difficult condition to treat and could be idiopathic or secondary. Conservative therapy is the first line of treatment attempted to allow the patient to return to his routine activities. When conservative treatment fails, patients can now turn toward surgical options such as microsurgical denervation of the spermatic cord (MDSC) which has a success rate published in the 60–85% range and/or minimally invasive therapies such as microcryoablation of the spermatic cord, Botox or Amniofix injection. There is an increase in referrals for CO. The true pathogenesis is still unclear and the road to complete recovery is unsure for certain patients. This paper proposes an algorithm for the management of patients suffering with CO.